PENEGAKAN KEADILAN RESTORATIF MELALUI DIVERSI DALAM SISTEM PERADILAN PIDANA ANAK: ANALISIS NORMATIF TERHADAP IMPLEMENTASI UNDANG-UNDANG NOMOR 11 TAHUN 2012 - Yadi Ilhami (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to analyze the normative construction and implementation of restorative justice through diversion mechanisms within the juvenile criminal justice system under Law Number Eleven of Two Thousand Twelve. The research focuses on examining the consistency of diversion regulations and their effectiveness in realizing a restorative paradigm for children in conflict with the law. This research employs a normative juridical method using statutory and conceptual approaches through the examination of relevant primary and secondary legal materials. The findings indicate that, normatively, diversion provisions have progressively adopted restorative justice principles; however, regulatory limitations and inconsistencies remain that potentially hinder optimal implementation. Structural and legal cultural factors also influence the effectiveness of diversion in practice. The study concludes that strengthening regulatory design, enhancing institutional capacity, and internalizing restorative principles in law enforcement practices are essential to ensure that the juvenile justice system genuinely prioritizes protection and substantive restoration.